An Improved LC-ESI-MS/MS Method to Quantify Pregabalin in Human Plasma and Dry Plasma Spot for Therapeutic Monitoring and Pharmacokinetic Applications. Issue 5 (October 2018) - Dwivedi, Jaya; Namdev, Kuldeep K.; Chilkoti, Deepak C.; Verma, Surajpal; Sharma, Swapnil
Abstract : Background: Therapeutic drug monitoring (TDM) of antiepileptic drugs provides a valid clinical tool in optimization of overall therapy. However, TDM is challenging because of the high biological sample (plasma/blood) storage/shipment costs and the limited availability of laboratories providing TDM services. Sampling in the form of dry plasma spot (DPS) or dry blood spot is a suitable alternative to overcome these issues. Methods: An improved, simple, rapid, and stability-indicating method for quantification of pregabalin (PGB) in human plasma and DPS has been developed and validated. Analyses were performed on liquid chromatography–tandem mass spectrometer under positive ionization mode of electrospray interface. PGB-d4 was used as internal standard, and the chromatographic separations were performed on Poroshell 120 EC-C18 column using an isocratic mobile phase flow rate of 1 mL/min. Stability of PGB in DPS was evaluated under simulated real-time conditions. Extraction procedures from plasma and DPS samples were compared using statistical tests. The method was validated considering the Food and Drug Administration method validation guideline. Results: The method was linear over the concentration range of 20–16, 000 ng/mL and 100–10, 000 ng/mL in plasma and DPS, respectively. DPS samples were found stable for only 1 week on storage at room temperature and for at least 4 weeks at freezing temperature (−20 ± 5°C). Method was applied for quantification of PGB in over 600 samples of a clinical study. Statistical analyses revealed that 2 extraction procedures in plasma and DPS samples showed statistically insignificant difference and can be used interchangeably without any bias. Conclusions: Proposed method involves simple and rapid steps of sample processing that do not require a precolumn or postcolumn derivatization procedure. The method is suitable for routine pharmacokinetic analysis and therapeutic monitoring of PGB.